2020
DOI: 10.2217/pmt-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Proclaim™ DRG Neurostimulator System for the Management of Chronic, Intractable Pain

Abstract: Chronic pain is consistently listed as one of the most costly and disabling health problems worldwide. In an effort to treat these suffering individuals, significant amounts of time and energy have been devoted to discover safe and effective pain relieving treatments. Dorsal root ganglion stimulation is the newest treatment modality to be created for chronic intractable pain. In this manuscript, we review the history and development, published research and safety profile of the Proclaim™ DRG Neurostimulator Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Although the DRG has been targeted for pain control since 1949, DRG stimulation was not described until 1991 in an animal model and 2009 for humans when Deer et al [8][9][10][11] performed the feasibility study. Importantly, in 2017 the results of the ACCURATE trial were published.…”
Section: Discussionmentioning
confidence: 99%
“…Although the DRG has been targeted for pain control since 1949, DRG stimulation was not described until 1991 in an animal model and 2009 for humans when Deer et al [8][9][10][11] performed the feasibility study. Importantly, in 2017 the results of the ACCURATE trial were published.…”
Section: Discussionmentioning
confidence: 99%
“…The APPs should be trained on evolving waveforms, frequencies, feedback response, and energy delivery offerings and any potential benefits over prior technologies. 12 , 13 , 14 , 15 In doing so, APPs can properly inform patients about device nuances as each manufacturer provides slightly different experiences for the patient. This includes paresthesia production, magnetic resonance imaging (MRI) conditionality, recharge requirements, battery size, and expected battery life.…”
Section: Therapy Educationmentioning
confidence: 99%
“…Deer et al published results from a randomized controlled trial comparing DRG stimulation to SCS for the treatment of CRPS Type I and II in the lower extremities in 2017 (12). Other studies have suggested that DRG stimulation may be effective at treating other chronic pain conditions (13‐22).…”
Section: Introductionmentioning
confidence: 99%